Randomized Control Trial Endline Data on Use of Improved Efficient Cookstoves in Malawi - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
This survey was conducted to collect endline data for a randomized control trial study. The endline survey was conducted two years after the introduction of improved energy cookstoves in the Dedza District in the Central Region of Malawi. A similar endline study was also conducted in Mozambique in the district of Angonia. Dedza district in Malawi was selected because it shares a transboundary with Angonia district in Mozambique and have similar biophysical and socioeconomic conditions. This selection was intended because the project was set out to examine how differences in policies in the two countries contributed to adoption and use of improved cookstoves under a randomized control trial experiment.